Teste em esteira e teste do degrau para avalia????o do broncoespasmo induzido pelo exerc??cio: eles s??o intercambi??veis? - Selman, Jessyca Pachi Rodrigues (2017)
Introduction: The tests of broncoprovocation with exercises most used are the tests in cycleergometer and treadmill. The step test is a simple test, with the advantage of being portable and performed in any environment. Objective: To compare the incremental step test (IST) with the treadmill test for evaluation of exercise-induced bronchospasm (EIB) in patients diagnosed with asthma; Secondarily, to contrast the cardiorespiratory demand during the exercise between both tests. Method: Was recruted Patients with asthma from the Asthma Out patient Clinic of the Allergy, Clinical Immunology and Rheumatology Department of the Federal University of S??o Paulo (UNIFESP), clinical lystable in the last six weeks. The order of the tests (treadmill or step) was performed on diferente days randomized. The patients performed the following sequence: pre-exercise spirometry, bronchoprovocation exercise test (according to randomization) together with analysis of expired gases and spirometry at times of 5, 10, 15, 20 and 30 minutes after exercise. Results: The step test had a lower metabolic, ventilatory and cardiovascular demand (p <0.05). There was pooragreement on kappa values ranging from 0.21 to 0.36. Although EIB prevalence was higher in the treadmill test (60%) compared to the IST (47%), functional characteristics rest did not differ between "discordant" versus "concordant" (p> 0. 05). The EIB was not related to the ability to reach very high levels of ventilation (??? 40% or ??? 60% maximum voluntary ventilation). In addition, a negative step, but a positive treadmill test (and vice-versa) was not associated with higher ventilatory demands in the positive test (p> 0.05). Conclusion: The prevalence of EIB was not related with ventilatory demand in the treadmill and step tests. Although, when the negative step test should be confirmed in a treadmill test in children with EIB symptoms.